Embolisation of gastroduodenal artery aneurysm caused by chronic pancreatitis. - Thakker, R; Gajjar, B; Wilkins, R; Levi, A (1983)
Chronic pancreatitis is known to cause vascular lesions, which produce gastrointestinal haemorrhage. Visceral vessel aneurysms are an unexpectedly common finding in arteriograms of patients with chronic pancreatitis. Gastrointestinal bleeding from these aneurysms carries a high mortality, making early diagnosis and treatment essential. Coeliac and mesenteric arteriography readily confirm the diagnosis. Surgical ligation or resection of the aneurysm entails a high mortality. Cessation of such gastrointestinal haemorrhage may be achieved by transcatheter embolisation under radiological control. This report describes a case in which bleeding from a gastroduodenal artery aneurysm, caused by chronic pancreatitis, was successfully treated by embolisation using a Gianturco coil.